Promovendo comportamentos adequados em sala de aula: efeitos da aplicação de uma variação positiva do Good Behavior Game em uma escola pública brasileira - Bomfim, Lívia Fernandes (2018)
The Good Behavior Game is a behavior management technique that has its effectiveness proven in changing various behavioral cathegories, on groups of different ages, in various settings, over 50 years of research. It is based in the division of the participants in teams, in the punctuation or withdrawal of points of these teams given the occurrence of inappropriate or unwanted behaviors and in the awards of the teams that have reached a certain score. This study investigated the changes in the occurrence of engagement and non-engagement on the task behaviors of 26 students of the 2nd year of Elementary School in a Brazilian public school, given the application of a positive variation of the Good Behavior Game, in which the teams are scored by the occurrence of appropriate behaviors. The students were divided into four teams and were scored by the teacher if all the members were following the rules: respect the teacher and colleagues, have good manners, do the homework and speak quietly. The results showed an increase in the occurrence of the engagement behaviors and a decrease in the occurrence of non-engagement. The results of this research base the recommendation of using the positive variation of the Good Behavior Game in Brazilian schools because it is an easy-to-implement technique that demands little or no monetary resources, requires minimal response cost in its application and is based on the use of positive reinforcement, rather than aversive control, with its participants